2022
DOI: 10.3322/caac.21757
|View full text |Cite
|
Sign up to set email alerts
|

Cancer statistics forAmericanIndian andAlaskaNative individuals, 2022: Including increasing disparities in early onset colorectal cancer

Abstract: American Indian and Alaska Native (AIAN) individuals are diverse culturally and geographically but share a high prevalence of chronic illness, largely because of obstacles to high-quality health care. The authors comprehensively examined cancer incidence and mortality among non-Hispanic AIAN individuals, compared with non-Hispanic White individuals for context, using population-based data from the National Cancer Institute, the Centers for Disease Control and Prevention, and the North American Association of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 173 publications
0
46
0
Order By: Relevance
“…In contrast to declining rates in all other racial and ethnic groups, mortality is increasing by more than 2% annually in Alaska Native persons 98,100 . Furthermore, among individuals younger than 50 years, rates are increasing by 4% per year for incidence and by 3% per year for mortality 11 . Reasons for the elevated risk remain unclear but may include a higher prevalence of risk factors, such as vitamin D deficiency because of low sun exposure; smoking; obesity; a diet high in smoked fish and marine mammals and low in fiber, fruits, and vegetables 101–103 ; and perhaps Helicobacter pylori infection 104–106 .…”
Section: Selected Findingsmentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast to declining rates in all other racial and ethnic groups, mortality is increasing by more than 2% annually in Alaska Native persons 98,100 . Furthermore, among individuals younger than 50 years, rates are increasing by 4% per year for incidence and by 3% per year for mortality 11 . Reasons for the elevated risk remain unclear but may include a higher prevalence of risk factors, such as vitamin D deficiency because of low sun exposure; smoking; obesity; a diet high in smoked fish and marine mammals and low in fiber, fruits, and vegetables 101–103 ; and perhaps Helicobacter pylori infection 104–106 .…”
Section: Selected Findingsmentioning
confidence: 92%
“…National CRC screening prevalence (2021) was obtained from the NCHS' National Health Interview Survey (NHIS). 11 The NHIS is conducted by the US Census Bureau and was designed to provide national prevalence estimates on health behaviors, such as cancer screening. Data are collected through computer-assisted, in-person interviews of adults aged 18 years and older.…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…This gap is particularly troubling finding given the significant mortality rate for American Indian/Native Americans, which is 18% higher compared to other groups. [32]. Several interventions are undergoing development and testing for Black cancer caregivers.…”
Section: Lesbian Gay Bisexual Transgender Queer + (Lgbtq +) Communitymentioning
confidence: 99%
“…3 In addition to later diagnosis, American Indian populations experience a lack of access to cancer care, particularly in rural and underserved areas, have high rates of poverty, which contribute to financial barriers, and harbor justified mistrust in the health care system. 4,5 Furthermore, research has demonstrated that American Indian patients are less likely to receive guideline-concordant cancer care and experience a higher likelihood of significant treatment delays. 6,7 The pronounced mortality rates observed among American Indian populations suffering from breast cancer underscore the need to identify barriers to treatment and understand the underlying causes of these barriers.…”
mentioning
confidence: 99%